Maternal RSV vaccine development. Where to from here? - Ahinsa Gunatilaka; Michelle L. Giles (Taylor & Francis Group, 2021)
Respiratory syncytial virus (RSV) is a common cause of acute lower respiratory tract infection and is responsible for a large proportion of infant morbidity and mortality worldwide. Most RSV-related deaths occur in children under six months, and the majority of these occur in low-income settings. To date, there is no known efficacious treatment for RSV infection; hence, prevention remains an important strategy to reduce the global burden of disease. Monoclonal antibodies and vaccinations are currently the two main approaches for prevention of RSV disease. Maternal RSV vaccination is of particular interest as a strategy to protect infants during their most vulnerable period as this approach has proven highly efficacious in other vaccine-preventable conditions such as pertussis and influenza. As results from ongoing phase III clinical trials become available, important decisions will need to be made about the priority and potential implementation of RSV vaccines alongside other public health measures.